do it step by step with reasons by side
y=(ax + b)n
(y+y)-y=[a(x+x)+b]n - (ax + b)n
[(y+y)-y]/(x)=([a(x+x)+b]n - (ax+b)n)/(x)
Applying limits on both sides with x approaching to zero, will give the value of dy/dx for
x0 y/ x = dy/dx.
x0y/x=x0 (ax+b)n ([(1+a.x/(ax+b))n - 1])/x
Expanding using Binomial, and ignoring higher order terms of x, for x is approaching to zero, and hence is very small.
=x0 (ax+b)n [1 + n(a.x/(ax+b))-1]/x
=x0 (ax+b)n n(a.x/(ax+b))/x
dy/dx = n.a.(ax+b)n-1
You have rated this answer /10